The Effects of Digital Tools on Third Graders’ Understanding of Concepts and Development of Skills in Multiplication - Yoon, Esther Jiyoung (2015)
The purpose of this research study was to examine the effectiveness of two digital tools: a virtual number line (Jumper Tool); and a dynamic hundreds chart (Morphing Chart) in improving children’s understanding of multiplication and number sense. One hundred twenty-two third grade students (69 girls), ages ranging from 8 years-0 months to 10 years-3 months (M = 8.88 years, SD = 0.44) from three New York City public elementary schools, were recruited to participate in the study. Participants were randomly assigned to one of two math treatment groups or a reading control group. Students in the Jumper group used a number line tool, while those in the Morphing group used a morphing hundreds chart. Children’s number sense ability and understanding of multiplication were tested at pre- and posttest to examine group differences. Researchers recorded children’s strategy use and a back-end logging system collected data on accuracy during treatment sessions. No group differences across the Jumper, Morphing, or Control groups were found at posttests when controlling for pretest performance. However, the presence of a tool (Jumper or Morphing) during treatment sessions resulted in better performance than the absence of a tool (No Tool). Strategy use had a significant effect on session performance as well. Fast and Tool Use responses performed better than Delayed responses. Additionally, Fast responses were more likely to be correct than those who used an Advanced strategy. Finally, the results indicated that Fast responses were predictive of children’s performance on multiplication facts and number sense tests and Tool use was predictive of performance on multiplication facts. These findings suggest that having a tool, Jumper or Morphing, helped children solve multiplication problems and that tool use is related to superior mastery of multiplication facts.